Complexes of aluminium, gallium and indium trifluorides with neutral oxygen donor ligands: Synthesis, properties and reactions. (26th February 2016) - Bhalla, Rajiv; Burt, Jennifer; Hector, Andrew L.; Levason, William; Luthra, Sajinder K.; McRobbie, Graeme; Monzittu, Francesco M.; Reid, Gillian
Graphical abstract: The first examples of complexes of AlF3 and GaF3 with oxygen donor ligands including dmso and pyridine N-oxide are described, along with the use of the dmso complexes as synthons for complexes of polydentate nitrogen ligands. Attempts to prepare complexes of these fluorides with phosphines are also described. Abstract: The MF3 ·3H2 O (M = Al, Ga or In) dissolve in hot dimethylsulfoxide (dmso) to form [MF3 (OH2 )2 (dmso)]; further dmso is not incorporated even after prolonged reflux. The X-ray structure of [GaF3 (OH2 )2 (dmso)] shows mer fluorides and trans OH2 ligands. The [GaF3 (OH2 )2 (dmso)] reacts with Me3 tacn (1, 4, 7-trimethyl-1, 4, 7-triazacyclononane) or 2, 2′-bipyridyl to give good yields of [GaF3 (Me3 tacn)]· x H2 O and [GaF3 (bipy)(OH2 )]·2H2 O at room temperature, previously obtained from GaF3 ·3H2 O by a hydrothermal route. [MF3 (OH2 )2 (dmso)] (M = Al or Ga) do not react with R3 PO (R = Me or Ph) in CH2 Cl2 or MeOH, but with pyNO (pyridine-N-oxide), the products were [AlF3 (OH2 )2 (pyNO)] and [GaF3 (OH2 )2 (pyNO)]·pyNO·H2 O. The structure of the latter shows equal numbers of the geometric isomers with mer – trans and mer – cis geometries, as well as lattice pyNO and H2 O. Pentamethyldiethylenetriamine (PMDTA) and [GaF3 (OH2 )2 (dmso)] react to produce the zwitterion [GaF4 (PMDTAH)]·2H2 O, which contains κ 2 -PMDTA with the 'free' NMe2 group protonated to balance the charge of the GaF4 − unit. Crystals of [⊂Me2 N(CH2 )2 NMe(CH2 )2 ]2 [Ga2 F8 (OH2 )2 ]·H2 O containing a 1, 1, 4-trimethylpiperazinium cation, were obtained as a minor by-product. The anion is an edge-shared fluoride-bridged dimer, with the coordinated water ligands arranged anti . Attempts to prepare complexes with phosphine or thioether ligands by Cl/F exchange from the corresponding chloro-complexes with [NMe4 ]F were unsuccessful, halide exchange being accompanied by liberation of the soft donor ligand. X-ray structures are also reported for [Me2 NH2 ][ trans -GaF4 (OH2 )2 ] and [AlCl3 (OAsPh3 )].